2012
DOI: 10.2174/157488712800100206
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Flow Measurements in the Internal Jugular Veins of Multiple Sclerosis Patients Using Magnetic Resonance Imaging

Abstract: Blood flow through the IJVs was reduced in the MS population with stenoses compared to those without.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
35
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 26 publications
3
35
1
Order By: Relevance
“…2 Among the potential factors that were related to MS, abnormal venous haemodynamics in the neck, including venous reflux and stenosis, has been hypothesized to be a feature of MS. [3][4][5][6] During the past few years, different studies were carried out to investigate the possible role of extracranial venous flow abnormalities in MS. These studies used different image modalities such as ultrasound 3,5,[7][8][9][10][11][12][13][14] and MRI, including contrast-enhanced MR venography (CE-MRV), phasecontrast MRI or time-of-flight sequences, 4,[15][16][17][18][19][20] and a combination of different imaging modalities. [21][22][23][24][25][26] These studies, however, yielded somewhat conflicting results, and the role of venous abnormalities in MS still remains in discussion.…”
Section: Introductionmentioning
confidence: 99%
“…2 Among the potential factors that were related to MS, abnormal venous haemodynamics in the neck, including venous reflux and stenosis, has been hypothesized to be a feature of MS. [3][4][5][6] During the past few years, different studies were carried out to investigate the possible role of extracranial venous flow abnormalities in MS. These studies used different image modalities such as ultrasound 3,5,[7][8][9][10][11][12][13][14] and MRI, including contrast-enhanced MR venography (CE-MRV), phasecontrast MRI or time-of-flight sequences, 4,[15][16][17][18][19][20] and a combination of different imaging modalities. [21][22][23][24][25][26] These studies, however, yielded somewhat conflicting results, and the role of venous abnormalities in MS still remains in discussion.…”
Section: Introductionmentioning
confidence: 99%
“…A functional MRV study revealed significant IJV flow impairment in 46% of 200 patients with 44 This abnormal flow was not seen in healthy controls studied by the same authors. 43 Importantly, flow restriction demonstrated by MRV studies [42][43][44] was less frequent than the prevalence of jugular abnormalities found in catheter venography studies (70%-90%). 1,[20][21][22][23][24][25][26][27]32,33 This favors the idea that jugular valves, even if stenotic, can affect flow differently.…”
mentioning
confidence: 90%
“…41 and magnetic resonance techniques evaluating both morphology and flow. 30,[42][43][44] Further, current magnetic resonance imaging is not very good at demonstrating pathology of the jugular valves (catheter venography studies tell us that this is the most common CCSVI abnormality). 25,[27][28][29]45 These valves are tiny structures, which are not easily visible on standard magnetic resonance images.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations